Effect of a synthetic insecticide and a botanical on pests, natural enemies and melon productivity - García-Vélez, Carlos J.; Chirinos, Dorys T.; Centeno-Parrales, Jesús A.; Cedeño, Luis A.; Pin, Darlinton (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
Melon is attacked by pests such as the whitefly, Bemisia tabaci (Gennadius), the cotton aphid, Aphis gossypii Glover, the flower thrips, Frankliniella occidentalis (Pergande) as well as Diaphania worms that can affect yield and crop productivity. To control it, frequent spraying of organo-synthetic insecticides is carried out, which can generate ecological imbalances. During two productive cycles, experimental plots were established to test the effect of an organo-synthetic insecticide and a botanical one on some pests, a natural enemy and on melon productivity. The treatments tested were, 1. Organo-synthetic insecticide: lambda-cyhalothrin + thiamethoxam. 2. Botanical insecticide: azadirachtin. 3. Untreated plot. The populations of A. gossypii, B. tabaci, F. occidentalis, fruits damaged by Diaphania spp. (% FDD), and the effect on parasitism in B. tabaci (% PBT), as well as on crop yield and productivity. The % FDD, the populations of A. gossypii and F. occidentalis did not show differences between treatments. The yields were higher in plots treated with azadirachtin, where there were lower populations of B. tabaci and higher % PBT. Productivity presented a negative correlation with the populations of B. tabaci. Despite the control exerted by azadirachtin on B. tabaci, there was a decrease in productivity, which added to the damage of Diaphania spp. suggest the importance of these pests and for their management other alternatives should be tested that reduce populations to levels that do not affect yield and at the same time guarantee sustainable production.